Estudos sobre a educação para as relações étnico-raciais e a descolonização do currículo de química - Alvino, Antônio César Batista (2017)
This study suggests the debate on the Decolonization of the Chemistry curriculum considering that America is a continent that had its social formation and culture founded on slave labor (Native Americans and Africans), the school as a microcosm of this society, in its curricula, also omits these presences. We argue that the best possible education is the one that ensures the rights of all (colonizers and colonized). However, the Brazilian school curriculum prioritizes the culture of the colonizer; in other words, the teaching of chemistry is based on European culture. The research proposes a curriculum that is committed to developing students' potentialities, understanding the organization, transformations, structure and properties of the matter and to understand the complex social and racial reality of Brazil. The objective of this research is to reconsider the teaching of chemistry by performing an epistemic displacement of the Chemistry curriculum. The empirical results presented in this text were collected in an Experimental Chemistry class that focuses on the Decolonization of the curriculum. This class had the purpose of making the epistemic displacement of the Chemistry curriculum working within the topic of the Law 10.639/03. Empirical results of three pedagogical interventions developed in the class are presented, eight excerpts from the discourse produced (biofuels, global warming, bleaching ideology, surface tension and body cleaning) are presented according to the topic of each class. The results show possibilities of teaching Chemistry from an epistemic matrix that is not European. The results indicate the need to think about the relationship between the construction of chemical knowledge and the social and racial relations within the classrooms and how they favor student development.